kepimpinan transformasional dan kualiti guru generasi 'Y' - Man, Jamilah (Faculty of Education, University of Malaya, 2016)
Transformational leadership practices among school leaders are importance in achieving the country towards making Malaysia a developed country to achieve Vision 2020.Efforts to increase leadership was introduced in Malaysia Education Blueprint 2013-2025. This study was conducted to determine the relationship between Transformational leadership and teachers’ quality among teachers of generation 'Y' in Maktab Rendah Sains MARA, North Zone, Peninsular Malaysia. This study used a cross sectional survey method using a standardized questionnaire.The instrument used was the Multifactor Leadership Questionnaire (MLQ) developed by Bass and Avolio in 1995 to measure the practice of leadership.While the quality of teachers was measured by using Model Establishment of Quality Teachers formed by Azizah Sarkowi in 2012.The findings showed that there was a significant positive relationship between transformational leadership and school leaders with the quality of teachers.Therefore, it is recommended that transformational leadership dimensions can be applied to the principal in every school to ensure that school leadership is at its best, in line with the National Education Blueprint 2013-2025.